Pentamethylphenyl (Ph*) and Related Derivatives as Useful Acyl Protecting Groups for Organic Synthesis: A Preliminary Study - Cheong, Choon Boon; Frost, James R.; Donohoe, Timothy J. (Synlett, 2020)
A study of acyl protecting groups derived from the Ph* motif is reported. While initial studies indicated that a variety of functional groups were not compatible with the Br2-mediated cleavage conditions required to release the Ph* group, strategies involving the use of different reagents or a modification of Ph* itself (Ph*OH) were investigated to solve this problem.
Keywords: protecting group; oxidative cleavage; acylium ion; HFIP; deprotection